Microstructure and corrosive wear resistance of plasma sprayed Ni-based coatings after TIG remelting. (23rd February 2018) - Tianshun, Dong; Xiukai, Zhou; Guolu, Li; Li, Liu; Ran, Wang
Abstract: Ni based coatings were prepared on steel substrate by means of plasma spraying, and were remelted by TIG (tungsten inert gas arc) method subsequently. The microstructure, microhardness, electrochemical corrosion and corrosive wear resistance under PH = 4, PH = 7 and PH = 10 conditions of the coatings before and after remelting were investigated. The results showed that the TIG remelting obviously reduced the defects and dramatically decreased the coating's porosity from 7.2% to 0.4%. Metallurgical bonding between the remelted coating and substrate was achieved. Meanwhile, the phase compositions of as-sprayed coating were γ -Ni, Mn5 Si2 and Cr2 B, while the phase compositions of the remelting coating were Fe3 Ni, Cr23 C6, Cr2 B and Mn5 Si2 . The microhardness of the coating decreased from 724 HV to 608 HV, but the fracture toughness enhanced from 2.80 MPa m 1/2 to 197.3 MPa m 1/2 after remelting. After corrosive wear test, the average wear weight loss and 3D morphology of wear scar of two coatings indicated that the wear resistance of the remelted coating was remarkably higher than that of as-sprayed coating. Therefore, TIG remelting treatment was a feasible method to improve the coating's microstructure and enhance its corrosive wear resistance.